2022
DOI: 10.14744/semb.2022.65481
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional smear and liquid-based cytology in adequacy of thyroid fine-needle aspiration biopsies without an accompanying cytopathologist

Abstract: Objectives In this study, we aimed to compare the adequacy of conventional smear (CS) and liquid-based cytology (LBC) methods in thyroid fine-needle aspiration biopsy (FNAB) samples obtained without an accompanying cytopathologist during the procedure. Furthermore, we aimed to investigate the presence of a significant difference between the rates of nodules classified as Bethesda Category III and malignancy in both techniques and the features of the nodules affecting malignancy. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
(38 reference statements)
1
3
2
Order By: Relevance
“…In correlation with our results, the rate of inadequate cases in CS is higher than that of SurePath in the literature. [12][13][14] The present results did not correlate with the results reported by Jung et al 5 and Kumari et al 15 who compared CS and SurePath in split samples. The conflict results were attributable to the different study methods.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…In correlation with our results, the rate of inadequate cases in CS is higher than that of SurePath in the literature. [12][13][14] The present results did not correlate with the results reported by Jung et al 5 and Kumari et al 15 who compared CS and SurePath in split samples. The conflict results were attributable to the different study methods.…”
Section: Discussioncontrasting
confidence: 93%
“…Conflicting results on the rate of inadequate samples of SurePath comparing with CS have been reported, as shown in Table 4. 5,[12][13][14][15] In the present study, sample adequacy was better for SurePath than CS. In correlation with our results, the rate of inadequate cases in CS is higher than that of SurePath in the literature.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Sayer et al [ 19 ] concluded that there was no statistical difference between the results of both methods while classifying thyroid nodules according to Bethesda category II to VI, but the non-diagnostic biopsy rate was higher in the specimens prepared by the CS method (p < 0.001). In their study, ultrasonography-guided FNA was performed and slides were prepared by either the CS or LBC method without an accompanying cytopathologist during the procedure.…”
Section: Discussionmentioning
confidence: 99%